Optimalisasi Penggunaan Media Augmented Reality, Brand Image, dan Brand Equity Terhadap Customer Loyalty di Platform Shopee - Sari, Dewi Komala; Dewi, Ayu Tri Tungga; Indayani, Lilik (Universitas Airlangga, 2024)
The ongoing development of the world of technology has a considerable impact on the daily use of the Internet in Indonesia, data based on a survey conducted by the Indonesia Internet Service Providers Association shows that the number of Internet users in Indonesia itself has increased from 132.7 million in 2016 to as many as 143.26 million in 2017, thus there has been an increase of 10, 56 million per year. The use of smart devices encourages the emergence of a new dimension in the business view of beauty product marketing activities in Indonesia. The research aims to determine how the enhancement of Augmented Reality, Brand Image, and Brand Equity influences Customer Loyalty towards Maybelline Products on the Shopee Platform. The research focused on all consumers who buy or use Maybelline products. For sampling in this study, nonprobability sampling is applied using the purposive sampling approach, with a total of 196 respondents. Data collection was performed through questionnaires that were evaluated using the Likert scale. The data analysis for this study employs multiple linear analysis, utilizing Smart PLS 3. 2. 8 software. Findings from this research show that the optimization of Augmented Reality does not impact the customer loyalty of Maybelline New York products in Sidoarjo Regency, while Brand Image and Brand Equity do influence Customer Loyalty for Maybelline Products.